Designers' guide to EN 1992-2 : Eurocode 2: Design of concrete structures : Part 2: Concrete bridges - Hendy, C. R. (Designers' guides to the eurocodes., 2007)
This guide describes the principles and requirements for safety serviceability and durability of concrete bridges.